2016
DOI: 10.1111/cen.13237
|View full text |Cite
|
Sign up to set email alerts
|

Total thyroidectomy: a clue to understanding the metabolic changes induced by subclinical hyperthyroidism?

Abstract: After total thyroidectomy, increases in weight and serum cholesterol were observed in the eSCH group. Given that post-operative TSH levels were similar in the two groups, these observations are probably due to the correction of eSCH, suggesting a direct effect of eSCH on body weight regulation and lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…3 We acknowledge the concerns raised by Bel Lassen et al 1 regarding patient numbers and heterogeneity (both surgical indication and treatment status). 2 We also congratulate them for their work on this topic.…”
Section: Re: Body Weight Change Is Unpredictable After Total Thyroidementioning
confidence: 87%
See 1 more Smart Citation
“…3 We acknowledge the concerns raised by Bel Lassen et al 1 regarding patient numbers and heterogeneity (both surgical indication and treatment status). 2 We also congratulate them for their work on this topic.…”
Section: Re: Body Weight Change Is Unpredictable After Total Thyroidementioning
confidence: 87%
“…3 We acknowledge the concerns raised by Bel Lassen et al 1 regarding patient numbers and heterogeneity (both surgical indication and treatment status). They found no predictors and in particular preoperative thyroid status did not predict weight gain after surgery.…”
mentioning
confidence: 87%
“…A few studies on the impact of thyroid function on lipid metabolism are available. Bel Lassen et al [19] proposed that endogenous subclinical hyperthyroidism after thyroidectomy may directly affect lipid profiles after thyroidectomy. Jung et al [20] suggested that changes in thyroid function after thyroidectomy can be associated with changes in the concentration and functions of lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…2 We also congratulate them for their work on this topic. 3 We acknowledge the concerns raised by Bel Lassen et al 1 regarding patient numbers and heterogeneity (both surgical indication and treatment status). These limitations have been acknowledged within the manuscript.We appreciate Bel Lassen et al pointing out the finding that post-operatively, on average, patients seemed to have been undertreated with thyroxine.…”
mentioning
confidence: 87%